Electrochemical sensor and application thereof in detection of nitrite content in sample

By fabricating a gold nanoparticle-polyphenylboronic acid-polyarginine membrane on a glassy carbon electrode and combining it with an electrochemical sensor containing iodine element/iodine ion probe, the problem of insufficient sensitivity in nitrite detection by bare electrodes was solved, achieving nitrite detection with higher sensitivity and lower detection limit, suitable for rapid detection of food and environmental samples.

CN120971530APending Publication Date: 2025-11-18SHANXI AGRI UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511378700.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-25
Publication Date
2025-11-18

AI Technical Summary

Technical Problem

Existing electrochemical methods for detecting nitrite have limited detection performance of bare electrodes, resulting in large overpotentials that lead to insufficient sensitivity and accuracy. Furthermore, traditional methods are time-consuming, complex to operate, and require expensive equipment, which limits their widespread application.

Method used

An electrochemical sensor was fabricated by using a glassy carbon electrode modified with gold nanoparticles-polyphenylboronic acid-polyarginine membrane (AuNPs-poly(PBA)-poly(Arg)) and combined with an iodine element/iodine ion probe via a one-step in-situ electrochemical co-deposition method, thereby achieving signal amplification and improved detection performance.

Benefits of technology

It achieves a wider linear range (1.00 pmol/L ~ 10.0 μmol/L) and a lower limit of detection (0.17 pmol/L), and the detection results have good repeatability and selectivity, making it suitable for rapid and accurate detection of nitrite in food and environmental samples.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120971530A_ABST
    Figure CN120971530A_ABST
Patent Text Reader

Abstract

The invention discloses an electrochemical sensor and application thereof in detection of nitrite content in a sample. The electrochemical sensor comprises a probe and a composite electrode; the composite electrode comprises an electrode substrate and a nano composite material modified on the surface of the electrode substrate, the nano composite material is a gold nanoparticle-polyphenylboronic acid-polyarginine nano composite film, and the probe is an iodine elementary substance / iodide probe. According to the method, under the assistance of an iodine elementary substance / iodide probe, the detection of nitrite in a sample is realized by utilizing a square wave voltammetry method and AuNPs-poly (PBA)-poly (Arg) / GCE. The electrochemical sensor has the advantages of being simple, rapid, sensitive, low in detection limit, good in reproducibility and the like, and has potential application prospects in the aspects of food safety and environmental protection.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of analytical detection, and particularly relates to an electrochemical sensor and application thereof in detection of nitrite content in cured beef and surface water. BACKGROUND

[0002] Nitrite (NO2 - ) as an inorganic compound exists widely in nature, and is widely used in the food industry. In daily life, nitrite as a common food additive exists in various cured meat products, cooked meat products and fermented meat products, and can play a role in maintaining the characteristic color and flavor of meat-derived food. However, when the human body intakes excessive nitrite, it will bring many serious hazards to the health, such as producing potential carcinogen N-nitrosamine and reducing the oxygen transport capacity of hemoglobin. Therefore, in order to protect human health, it is necessary to develop a detection method for nitrite content.

[0003] At present, there are many detection methods for nitrite, including colorimetric method, spectrophotometric method, chromatographic method, fluorescence method, etc. However, these technologies are time-consuming, complex in operation and expensive in equipment, which limits their wide application in nitrite detection. Among the known methods, the electrochemical method has attracted wide attention due to its advantages of simplicity, rapidness, accuracy, high sensitivity, etc.

[0004] Electrochemical detection can realize direct electrocatalytic oxidation of nitrite on the surface of the electrode, but the detection performance of nitrite on the bare electrode is limited, which is mainly due to the existence of a large overpotential in the direct measurement of nitrite on the bare electrode, which reduces the detection sensitivity and accuracy. Therefore, various materials can be developed to modify the electrode to improve the detection performance of nitrite.

[0005] CN120468242A discloses a sodium iodide probe assisted gold nanoparticle-polyarginine-polylysine electrochemical sensor and application thereof in detection of nitrite in beef and tap water. The sensor has been improved in detection limit, sensitivity and linear range, but it is not ideal enough. At the same time, the use of sodium iodide as a probe signal alone is not stable enough, and further optimization is needed. In view of this, the present application is proposed. SUMMARY

[0006] The application aims to provide an electrochemical sensor and its application in detecting nitrite content in halogenated beef and surface water. The electrochemical sensor has the advantages of simplicity, rapidity, good repeatability, wider linear range (1.00 pmol / L-10.0 μmol / L), lower detection limit (0.17 pmol / L), good recovery rate when used for detecting nitrite content in beef and surface water samples, and potential application prospect in food safety and environmental protection.

[0007] In order to achieve the above-mentioned purpose, the technical scheme adopted by the application is as follows: In a first aspect, the application provides a composite electrode, which comprises an electrode substrate and a nano-composite material modified on the surface of the electrode substrate; the nano-composite material comprises gold nanoparticles (AuNPs), poly(phenylboronic acid) (poly(PBA)) and poly(arginine) (poly(Arg)). That is, a gold nanoparticle-poly(phenylboronic acid)-poly(arginine) film (AuNPs-poly(PBA)-poly(Arg)).

[0008] The electrode substrate is a glassy carbon electrode (GCE).

[0009] In a second aspect, the application provides a preparation method of the electrochemical sensor, which comprises the following steps: immersing an electrode substrate in a solution containing a gold source, phenylboronic acid and arginine, and using a cyclic voltammetry method to co-deposit in situ on the surface of the electrode substrate to obtain a gold nanoparticle-poly(phenylboronic acid)-poly(arginine) film.

[0010] The gold source is chloroauric acid, and the concentration thereof is 0.30-0.50 g / L; the concentration of the phenylboronic acid is 30-50 mmol / L; and the concentration of the arginine is 8-12 mmol / L.

[0011] The parameter conditions of the in-situ co-deposition are as follows: the potential range is 1.4 V- -1.4 V, the scanning rate is 0.08-0.12 V / s, and the cycle number is 8-12 cycles.

[0012] In a third aspect, the application provides an electrochemical sensor, which comprises a probe and the composite electrode.

[0013] The probe is I2 / I - The probe.

[0014] In a fourth aspect, the application provides an electrochemical method for detecting nitrite content in a sample, which uses the electrochemical sensor.

[0015] The detection method comprises the following steps: (1) Add gradient concentrations of nitrite standard and I2 / I to the sample solution respectively. - Then, a composite electrode is inserted to perform cyclic voltammetry testing; (2) After obtaining a stable cyclic voltammetry plot, I2 / I is obtained by square wave voltammetry. - Based on the characteristic response current values, a standard curve of current versus nitrite concentration was plotted. (3) Calculate the nitrite content in the sample based on the standard curve.

[0016] The sample solution was prepared under one of the following conditions: The sample is a solid. The procedure is as follows: Chop the solid sample and soak it in PBS buffer solution for 4-5 hours, then sonicate it for 20-30 minutes to obtain a solid sample solution. The sample is a liquid, and the procedure is as follows: dilute the liquid sample with PBS buffer solution to obtain a liquid sample solution; The PBS buffer solution is a buffer solution prepared from phosphoric acid, sodium dihydrogen phosphate and disodium hydrogen phosphate with a pH of 2.5-4.5 and a concentration of 0.1 mol / L. The I2 / I - After adding the sample solution, the concentration of elemental iodine (I₂) was 0.9-1.1 mmol / L, and the concentration of iodide ions (I₂) was... - The concentration was 1.2-1.8 mmol / L; The nitrite standards have the following concentration gradients: 0 pmol / L, 1.00 pmol / L, 10.0 pmol / L, 100.0 pmol / L, 1.0 nmol / L, 10.0 nmol / L, 100.0 nmol / L, 1.0 μmol / L, and 10.0 μmol / L. The parameters for the cyclic voltammetry test are: voltage range of 0-1.05 V, scan rate of 75-125 mV / s; The parameters for the square wave voltammetry detection are: frequency 5-15Hz, amplitude 10-30 mV, step potential 3-7 mV, oxidation potential range 0.2-0.7 V, and reduction potential range 0.7-0.2 V. The samples were food and environmental samples.

[0017] Compared with the prior art, the beneficial effects achieved by the present invention are: The AuNPs-poly(PBA)-poly(Arg) composite film is prepared by one-step in-situ electrochemical co-deposition method, and the excellent conductivity of the AuNPs-poly(PBA)-poly(Arg) composite film is used to realize the electric signal amplification, so that the detection performance of the sensor is improved. BRIEF DESCRIPTION OF DRAWINGS

[0018] Figure 1 SEM images of (A) AuNPs, (B) AuNPs-poly(PBA), (C) AuNPs-poly(Arg) and (D) AuNPs-poly(PBA)-poly(Arg) electrodeposited on the surface of bare GCE.

[0019] Figure 2 Oxidation square wave voltammograms of (A) bare GCE, (B) AuNPs / GCE and (C) AuNPs-poly(PBA)-poly(Arg) / GCE for detection of different concentrations of NaNO2 in the presence of 1.0 mmol / L I2 and 1.5 mmol / L NaI.

[0020] Figure 3 Reduction square wave voltammograms of (A) bare GCE, (B) AuNPs / GCE and (C) AuNPs-poly(PBA)-poly(Arg) / GCE for detection of different concentrations of NaNO2 in the presence of 1.0 mmol / L I2 and 1.5 mmol / L NaI.

[0021] Figure 4 Influence of AuNPs-poly(PBA)-poly(Arg) film co-deposition conditions on nitrite determination; wherein (A) cycle number and (B) scan rate.

[0022] Figure 5 Influence of buffer pH on nitrite determination.

[0023] Figure 6 (A) Square wave voltammograms of the electrochemical sensor for detection of 0 ~10.0 μmol / L NaNO2 in the presence of 1.0 mmol / L I2 and 1.5 mmol / L NaI (from top to bottom, the concentrations of NaNO2 are 0 pmol / L, 1.00 pmol / L, 10.0 pmol / L, 100.0 pmol / L, 1.0 nmol / L, 10.0 nmol / L, 100.0 nmol / L, 1.0 μmol / L, 10.0 μmol / L, respectively); (B) Relationship diagram of reduction peak current and NaNO2 concentration. DETAILED DESCRIPTION

[0024] The application will be further described in connection with the following specific examples, but the application is not limited to the following examples.

[0025] The experimental methods used in the following examples are conventional methods unless otherwise specified.

[0026] The reagents, materials, instruments, etc. used in the following examples can be obtained from commercial channels unless otherwise specified.

[0027] Materials and reagents used in the following examples: The reagents of phenylboronic acid, L-arginine, chloroauric acid aqueous solution, sodium iodide, elemental iodine, sodium nitrite, hydrochloric acid, sodium sulfate, magnesium chloride, aluminum chloride, sodium fluoride, cobalt chloride, potassium nitrate, zinc nitrate, copper sulfate, potassium ferricyanide, etc. were purchased from Shanghai Aladdin Bio-Chem Technology Co., Ltd.

[0028] Phosphate buffer solution (PBS): 0.1 mol / L phosphate buffer solution with pH of 2.5 ~ 4.5 was prepared from phosphoric acid, sodium dihydrogen phosphate, and disodium hydrogen phosphate; the concentration of phosphoric acid, sodium dihydrogen phosphate, and disodium hydrogen phosphate was 0.1 mol / L.

[0029] Elemental iodine / sodium iodide mixed solution: PBS (0.1 mol / L, pH 4.0) was used to prepare elemental iodine / sodium iodide mixed solution containing different standard concentrations of sodium nitrite; the concentration of elemental iodine was 1.0 mmol / L, and the concentration of sodium iodide was 1.5 mmol / L. The standard concentrations of sodium nitrite were 0 pmol / L, 1.00 pmol / L, 10.0 pmol / L, 100.0 pmol / L, 1.0 nmol / L, 10.0 nmol / L, 100.0 nmol / L, 1.0 μmol / L, and 10.0 μmol / L.

[0030] Halal beef samples were produced by a local enterprise in Shanxi.

[0031] Surface water samples were taken from Taigu, Shanxi.

[0032] Example 1, Preparation of AuNPs-poly(PBA)-poly(Arg) / GCE AuNPs-poly(PBA)-poly(Arg) / GCE was prepared by one-step in-situ electrochemical co-deposition method, and the specific steps were as follows: (1) Pretreatment of bare electrode: Take appropriate amount of 0.30 μm and 0.05 μm alumina powder and place them on different positions of a piece of chamois leather, wet them with distilled water, and then polish a 3 mm diameter bare glassy carbon electrode (GCE) vertically on the surface of the chamois leather with the two kinds of alumina powder placed thereon in the shape of "8" for 200 times, respectively. The polished electrode is washed with distilled water and ultrasonically cleaned in ethanol and distilled water for 5 min, respectively, to obtain a clean GCE.

[0033] The method for detecting whether the working surface of the glassy carbon electrode is smooth or not is as follows: place the polished GCE in a 5 mmol / L potassium ferricyanide solution (0.10 mol / L potassium nitrate as supporting electrolyte), characterize the working electrode by cyclic voltammetry, and observe the potential difference between the oxidation peak and the reduction peak in the graph. When the difference is within 100 mV, it is used for subsequent experiments.

[0034] (2) Preparation of AuNPs-poly(PBA)-poly(Arg) / GCE: immerse the bare GCE in a mixed solution containing 0.40 g / L chloroauric acid, 40 mmol / L phenylboronic acid, 10 mmol / L L-arginine, 0.20 mol / L hydrochloric acid and 0.10 mol / L potassium nitrate, and use cyclic voltammetry to co-deposit an AuNPs-poly(PBA)-poly(Arg) film in situ under the following conditions: potential range of 1.4 V to -1.4 V, scan rate of 0.100 V / s, and 10 cycles. After washing with a large amount of distilled water, the prepared AuNPs-poly(PBA)-poly(Arg) / GCE is used for the detection of nitrite.

[0035] Example 2, Detection of nitrite in beef samples The detection steps are as follows: (1) Processing of marinated beef sample: first, weigh 1.000 g of marinated beef sample, cut it into small pieces, and soak it in 10 mL of PBS (0.10 mol / L, pH 4.0) for 4 h; then, ultrasonically disperse the marinated beef sample solution for 20 min, and then dilute the marinated beef sample solution step by step with PBS (0.10 mol / L, pH 4.0); finally, analyze the marinated beef sample solution diluted 1000000 times.

[0036] (2) Detection of nitrite in beef sample: The content of nitrite in the sample was detected by electrochemical method with the assistance of iodine / sodium iodide probe. First, the sample solution was added with gradient concentration of nitrite standard and iodine / sodium iodide. Then, the AuNPs-poly(PBA)-poly(Arg) / GCE was inserted into the sample solution containing gradient concentration of nitrite standard and iodine / sodium iodide, and cyclic voltammetry (CV) test was performed under the condition of voltage range of 0-1.05 V and scan rate of 100 mV / s. After obtaining the stable cyclic voltammogram, the characteristic response current value of iodine / sodium iodide was obtained by square wave voltammetry and iodine / sodium iodide probe detection, and the standard curve of current-nitrite concentration was drawn. According to the standard curve, the content of nitrite in the sample was calculated. The square wave voltammetry experimental parameters were as follows: frequency 10 Hz, amplitude 20 mV, step potential 5 mV, oxidation potential range 0.2 V to 0.7 V, and reduction potential range 0.7 V to 0.2 V.

[0037] Example 3, Detection of nitrite in surface water sample The detection steps were as follows: (1) Surface water sample treatment: 1.00 mL of surface water sample was diluted with PBS (0.10 mol / L, pH 4.0) in stages, and the diluted 10000-fold surface water sample solution was analyzed.

[0038] (2) Detection of nitrite in the sample: The content of nitrite in the sample was detected by electrochemical method with the assistance of iodine / sodium iodide probe. First, the sample solution was added with gradient concentration of nitrite standard and iodine / sodium iodide. Then, the AuNPs-poly(PBA)-poly(Arg) / GCE was inserted into the sample solution containing gradient concentration of nitrite standard and iodine / sodium iodide, and cyclic voltammetry (CV) test was performed under the condition of voltage range of 0-1.05 V and scan rate of 100 mV / s. After obtaining the stable cyclic voltammogram, the characteristic response current value of iodine / sodium iodide was obtained by square wave voltammetry and iodine / sodium iodide probe detection, and the standard curve of current-nitrite concentration was drawn. According to the standard curve, the content of nitrite in the sample was calculated. The square wave voltammetry experimental parameters were as follows: frequency 10 Hz, amplitude 20 mV, step potential 5 mV, oxidation potential range 0.2 V to 0.7 V, and reduction potential range 0.7 V to 0.2 V.

[0039] Results and analysis 1. Preparation and characterization of AuNPs-poly(PBA)-poly(Arg) / GCE The morphology of AuNPs, AuNPs-poly(PBA), AuNPs-poly(Arg) and AuNPs-poly(PBA)-poly(Arg) materials electrodeposited on the surface of GCE was characterized by JEOL JSM-7900F scanning electron microscopy (SEM).

[0040] From Figure 1 As can be seen from (A), only a small amount of AuNPs was dispersed on the surface of GCE when only AuNPs was deposited. When AuNPs-poly(PBA) was deposited, the amount of AuNPs deposited increased and the distribution was more uniform, and a small amount of poly(PBA) was observed to exist in the form of a thin film and uniformly distributed on the surface of GCE (such as Figure 1 (B)). When AuNPs-poly(Arg) was deposited, a small amount of poly(Arg) existed in the form of an irregular thin film and was deposited on the surface of GCE (such as Figure 1 (C)). When AuNPs and poly(PBA)-poly(Arg) were co-deposited (such as Figure 1 (D)), more AuNPs were distributed on the surface of the electrode and only a small amount of agglomeration occurred, showing higher uniformity, which was mainly caused by the synergistic effect of phenylboronic acid and L-arginine; at the same time, the existence of poly(PBA)-poly(Arg) copolymer film was observed, and the coverage of the copolymer film was significantly improved compared with Figure 1 (B), Figure 1 (C). These experimental results collectively show that AuNPs-poly(PBA)-poly(Arg) / GCE can be successfully prepared.

[0041] 2. Detection mechanism of AuNPs-poly(PBA)-poly(Arg) / GCE for nitrite Autolab PGSTAT 302N electrochemical workstation and a three-electrode system were used to complete all electrochemical measurements. The three-electrode system consisted of a silver / silver chloride (3.0 mol / L potassium chloride reference solution) electrode, a platinum wire electrode and a bare GCE or AuNPs-poly(PBA)-poly(Arg) / GCE.

[0042] Figure 2 The I2 / I - Oxidation square wave voltammograms of different concentrations of nitrite in the presence of I2 / I

[0043] When I2 / I- No obvious oxidation peak was observed for all three working electrodes when the probe and nitrite were present.

[0044] When I2 / I - The probe, in the absence of nitrite, I - The peak potential of oxidation reaction occurred at 0.55 V with an oxidation peak current value of 37.4 A on the bare GCE working electrode surface; for AuNPs / GCE, I -- The oxidation reaction occurred at 0.51 V with a peak current value of 39.7 A, indicating that the AuNPs deposited on the surface of the bare GCE had catalytic effect on the oxidation reaction of I - When AuNPs, poly(PBA) and poly(Arg) were co-deposited on the electrode surface, the oxidation reaction potential of I - changed to 0.49 V and the oxidation peak current value increased to 64.8 A, indicating that AuNPs-poly(PBA)-poly(Arg) / GCE had good electrocatalytic activity for the oxidation reaction of I - on the electrode surface, which was mainly due to the synergistic effect of AuNPs, poly(PBA) and poly(Arg).

[0045] When I2 / I - the probe and nitrite were present in the PBS solution, compared with the results without nitrite, the oxidation peak current values of the three working electrodes showed a downward trend with the increase of the concentration of nitrite, indicating that nitrite participated in the oxidation of I2 / I - probe and caused the decrease of the peak current signal, and the size order of the decrease of the peak current signal was AuNPs-poly(PBA)-poly(Arg) / GCE > AuNPs / GCE > GCE. The chemical reaction occurred in the solution might be the reason for the decrease of the current value, and I - reacted with NO2 - to generate I2, and in this process, the concentration of I - would decrease with the increase of the concentration of NO2 - , so the oxidation peak current value of I2 / I - probe would decrease with the increase of the concentration of nitrite.

[0046] Figure 3 The reduction square wave voltammograms of different concentrations of nitrite were detected by three different working electrodes (GCE, AuNPs / GCE, AuNPs-poly(PBA)-poly(Arg) / GCE) in the presence of I2 / I - probe.

[0047] When I2 / I -No obvious reduction peak was observed on the three working electrodes when the probe and nitrite were present.

[0048] When I2 / I - When the probe and no nitrite were present, the peak potential of I2 reduction on the bare GCE working electrode surface was 0.51 V and the reduction peak current value was 36.6 A; for AuNPs / GCE, I2 reduction occurred at 0.49 V and the peak current value was 41.2 A, which indicated that the AuNPs deposited on the surface of the bare GCE had a catalytic effect on the reduction of I2; when AuNPs, poly(PBA) and poly(Arg) were co-deposited on the electrode surface, the peak potential of I2 reduction shifted negatively to 0.47 V and the reduction peak current value increased to 65.1 A, which indicated that AuNPs-poly(PBA)-poly(Arg) / GCE had good electrocatalytic activity for the reduction of I2 on the electrode surface, which was mainly due to the synergistic effect of AuNPs, poly(PBA) and poly(Arg).

[0049] When I2 / I - When the probe and nitrite were present, compared with the results without nitrite, the reduction peak current values of the three working electrodes showed a downward trend as the concentration of nitrite increased, indicating that nitrite participated in the reduction of I2 / I - The probe was reduced and caused its peak current signal to decrease, and the peak current signal decreased in the order of AuNPs-poly(PBA)-poly(Arg) / GCE > AuNPs / GCE > GCE. The reason for the reduction of the reduction peak current value may be that I - NO2 - reacted in the solution, reducing the concentration of I - on the electrode surface, resulting in a decrease in the concentration of I2 generated on the electrode surface, and a decrease in the concentration of I2 available for electrochemical reduction, thereby obtaining a low reduction peak current value.

[0050] AuNPs-poly(PBA)-poly(Arg) / GCE in I2 / I - During the detection of different concentrations of nitrite in the presence of the probe, the peak current signal change under reduction conditions was more sensitive than that under oxidation conditions, so the peak current signal change under reduction conditions was subsequently selected as the main basis for detecting the concentration of nitrite.

[0051] 3. Selection of AuNPs-poly(PBA)-poly(Arg) film co-deposition conditions The co-deposition conditions of AuNPs-poly(PBA)-poly(Arg) films have a significant impact on the performance of this nitrite electrochemical sensor. To achieve ultrasensitive detection of nitrite, the effects of AuNPs-poly(PBA)-poly(Arg) film co-deposition conditions, including the number of cycles and scan rate, on nitrite determination were mainly investigated using square wave voltammetry. - The optimal co-deposition conditions are selected by analyzing the relative current change of the probe reduction peak.

[0052] Figure 4 (A) is I2 / I - The relative current change of the probe reduction peak was observed within the range of 8 to 12 cycles. As the number of cycles increased from 8 to 12, the initial difference in relative current change was small, reaching a maximum at 10 cycles, and then decreasing significantly. When the number of cycles was less than 10, the thickness of the AuNPs-poly(PBA)-poly(Arg) film was insufficient to achieve ideal conductivity, resulting in a small relative current change. As the number of cycles increased from 10 to 12, the AuNPs-poly(PBA)-poly(Arg) film became too thick, which also hindered achieving ideal conductivity, leading to a small relative current change. Since the relative current change was greatest at 10 cycles, 10 cycles were chosen as the optimal number of cycles for co-depositing the AuNPs-poly(PBA)-poly(Arg) film.

[0053] Figure 4 (B) gives the I² / I² ratio for scan rates from 0.08 V / s to 0.12 V / s. - The relative current change of the probe's reduction peak was observed. Within the range of 0.08 V / s to 0.12 V / s, the relative current change initially increased significantly with increasing scan rate, then decreased and stabilized at scan rates greater than 0.10 V / s. The maximum relative current change was observed at a scan rate of 0.10 V / s, indicating that this scan rate is advantageous for obtaining AuNPs-poly(PBA)-poly(Arg) films with excellent conductivity. Conversely, scan rates that are too low or too high are detrimental. Therefore, 0.10 V / s was selected as the optimal scan rate for co-depositing AuNPs-poly(PBA)-poly(Arg) films.

[0054] 4. Effect of buffer pH The form of nitrite, the charged state of AuNPs-poly(PBA)-poly(Arg) films, and their interactions are closely related to the pH of the buffer solution. Square wave voltammetry was used to investigate the effect of buffer pH (2.5–4.5) on the I2 / I2 ratio induced by 0.1 μmol / L nitrite. - The relative current change of the probe reduction peak was investigated to study the effect of buffer solution pH on nitrite detection.

[0055] Figure 5 The relative current change represents the reduction peak. As the pH ranges from 2.5 to 4.0, the relative current change continuously increases, reaching a maximum at pH 4.0, and then rapidly decreases within the 4.0–4.5 range. This is mainly due to the I₂ / I₂ ratio. - The reaction between them is highly reversible, allowing for rapid electron transfer at the electrode surface for the electrochemical detection of nitrite. In acidic media, I₂ / I₂... - Forming a dynamic cycle, I - With NO2 - Oxidation reaction occurs and NO2 - The participation of I - The oxidation rate of I₂ is reduced to form I₂. - When the pH value is 4, the solution reacts with NO2. - I that undergoes a chemical reaction - The highest consumption leads to the electrochemical reaction that can occur on the electrode surface. - The lowest concentration causes the greatest change in relative current. However, excessively high or low pH values ​​lead to changes in NO2 concentration. - I that undergoes a chemical reaction - The relatively low concentration resulted in a small change in relative current. Therefore, pH 4.0 was chosen as the optimal pH for the buffer solution in subsequent experiments.

[0056] 5. Analytical performance of electrochemical sensor in detecting nitrite (1) Linear range and detection limit Figure 6 (A) shows the square-wave voltammetry of 0–10.0 μmol / L NaNO2 detected by the electrochemical sensor in the presence of 1.0 mmol / L I2 and 1.5 mmol / L NaI. A distinct reduction peak is observed when NaNO2 is absent from the solution. Even at NaNO2 concentrations as low as 1.0 pmol / L, a significant decrease in the reduction peak current is still observed. The reduction peak current continuously decreases as the NaNO2 concentration increases.

[0057] like Figure 6 As shown in (B), I2 / I -The probe reduction peak current and the logarithm of NaNO2 concentration showed two linear relationships in the ranges of 1.00 pmol / L to 10.0 nmol / L and 100.0 nmol / L to 10.0 μmol / L, and the regression equations were I (μA)=-2.20-38.14Log c (mol / L) (the correlation coefficient R was -0.9997) and I (μA)= -3.10-31.54Log c (mol / L) (the correlation coefficient R was -0.9997). The detection limit of the electrochemical sensor for nitrite was 0.17 pmol / L (S / N = 3).

[0058] (2) Reproducibility The reproducibility of the electrochemical sensor for nitrite detection was evaluated by investigating the responses of the same and different AuNPs-poly(PBA)-poly(Arg) / GCE to 0.1 μmol / L NaNO2. The same AuNPs-poly(PBA)-poly(Arg) / GCE was used to measure 0.1 μmol / L NaNO2 for 12 times, and I2 / I - The relative standard deviation (RSD) of the probe reduction peak current was 0.45%. Five AuNPs-poly(PBA)-poly(Arg) / GCE were used to measure 0.1 μmol / L NaNO2 for 12 times, and I2 / I - The relative standard deviation (RSD) of the probe reduction peak current was 2.4%. These results showed that the electrochemical sensor had excellent reproducibility for nitrite detection.

[0059] (3) Selectivity The selectivity of the electrochemical sensor for nitrite detection was evaluated by using AuNPs-poly(PBA)-poly(Arg) / GCE to measure 0.1 μmol / L NaNO2 and 10.0 μmol / L of other competitive substances such as sodium sulfate, magnesium chloride, calcium chloride, aluminum chloride, ammonium chloride, sodium fluoride, potassium nitrate, and zinc nitrate. The results showed that compared with the results of 0.1 μmol / L NaNO2, the change amplitude of the reduction peak current caused by 100 times concentration of the above competitive substances was within 9.11%, indicating that the electrochemical sensor had good selectivity for nitrite detection.

[0060] (4) Stability The stability of the electrochemical sensor was investigated by cyclic voltammetry scanning PBS (0.1 mol / L, pH 4.0) containing 1.0 mmol / L I2 and 1.5 mmol / L NaI for 50 cycles. The results show that the reduction peak current of the 50th cycle is 106.38% of the first cycle, indicating that the sensor has good electrochemical stability. - The probe reduction peak current is 106.38% of the first cycle, indicating that the sensor has good electrochemical stability.

[0061] 6、Sample analysis To illustrate the potential application prospects of the electrochemical sensor, the dilution 1000000 times of beef sample solution and the dilution 10000 times of surface water sample solution were respectively subjected to the standard addition recovery rate test. The sample analysis results show that the concentration of nitrite in the diluted beef sample solution is 1.43 pmol / L, and the surface water sample solution is not detected. In the range of 10 ~ 1000 pmol / L, the average standard addition recovery rate of nitrite in the three samples is in the range of 89.70% ~ 107.33%, and the RSD is in the range of 0.14% ~ 7.71%. These results show that the method is expected to be used for the detection of picomolar level of nitrite in food and environmental samples.

[0062] Table 1 Electrochemical sensor for detecting the content of nitrite in diluted beef and surface water samples (n = 3)

[0063] 7、Conclusion The application combines I2 / I - A novel nitrite electrochemical sensor is constructed by the probe and AuNPs-poly(PBA)-poly(Arg) / GCE. The AuNPs-poly(PBA)-poly(Arg) / GCE is prepared by one-step in-situ electrochemical co-deposition method. The I2 / I - With the aid of the probe, the AuNPs-poly(PBA)-poly(Arg) / GCE is used for electrochemical detection of nitrite, and the detection effect is much better than most of the reported electrochemical sensors. Based on I2 / I - The reduction linear range of the probe-assisted AuNPs-poly(PBA)-poly(Arg) / GCE electrochemical sensor for nitrite concentration is 1.00 pmol / L ~ 10.0 μmol / L, and the detection limit is 0.17 pmol / L. The electrochemical sensor has the advantages of simplicity, rapidness, wide linear range, low detection limit, good repeatability and the like. In addition, the electrochemical sensor can be used for determining the content of nitrite in beef and surface water samples, and has good recovery rate, and has potential application prospects in food safety and environmental protection.

[0064] While the application has been described in detail and with reference to specific embodiments thereof, it will be apparent to one skilled in the art that various modifications or changes can be made therein without departing from the spirit and scope thereof. Accordingly, it is intended that all such modifications and changes be included within the scope of the application as claimed.

Claims

1. A composite electrode, characterized in that, Nanocomposite materials, including electrode substrates and their surface modifications; The nanocomposite material includes gold nanoparticles, polyphenylboronic acid, and polyarginine.

2. The composite electrode according to claim 1, characterized in that, The electrode substrate is a glassy carbon electrode.

3. The method for preparing the composite electrode according to claim 1 or 2, characterized in that, The process includes the following steps: immersing the electrode substrate in a solution containing gold source, phenylboronic acid and arginine, and using cyclic voltammetry to co-deposit in situ on the surface of the electrode substrate to obtain a gold nanoparticle-polyphenylboronic acid-polyarginine film.

4. The preparation method according to claim 3, characterized in that, The gold source is chloroauric acid with a concentration of 0.30-0.50 g / L; the concentration of phenylboronic acid is 30-50 mmol / L; and the concentration of arginine is 8-12 mmol / L.

5. The preparation method according to claim 3 or 4, characterized in that, The parameters for the in-situ co-deposition are: potential range of 1.4 V to 1.4 V, scan rate of 0.08 to 0.12 V / s, and number of cycles of 8 to 12.

6. An electrochemical sensor, characterized in that, Includes a probe and a composite electrode according to any one of claims 1-5.

7. The electrochemical sensor according to claim 6, characterized in that, The probe is an iodine / iodide probe.

8. An electrochemical method for detecting nitrite content in a sample, characterized in that, Detection is performed using the electrochemical sensor described in claim 6 or 7.

9. The method according to claim 8, characterized in that, The detection method includes the following steps: (1) Add gradient concentrations of nitrite standard and I2 / I to the sample solution respectively. - Then, a composite electrode is inserted to perform cyclic voltammetry testing; (2) After obtaining a stable cyclic voltammetry plot, I2 / I is obtained by square wave voltammetry. - Based on the characteristic response current values, a standard curve of current versus nitrite concentration was plotted. (3) Calculate the nitrite content in the sample based on the standard curve.

10. The method according to claim 9, characterized in that, The sample solution was prepared under one of the following conditions: The sample is a solid. The procedure is as follows: Chop the solid sample and soak it in PBS buffer solution for 4-5 hours, then sonicate it for 20-30 minutes to obtain a solid sample solution. The sample is a liquid, and the procedure is as follows: dilute the liquid sample with PBS buffer solution to obtain a liquid sample solution; The PBS buffer solution is a buffer solution prepared from phosphoric acid, sodium dihydrogen phosphate and disodium hydrogen phosphate with a pH of 2.5-4.5 and a concentration of 0.1 mol / L. The I2 / I - After adding the sample solution, the concentration of elemental iodine (I₂) was 0.9-1.1 mmol / L, and the concentration of iodide ions (I₂) was... - The concentration was 1.2-1.8 mmol / L; The nitrite standards have the following concentration gradients: 0 pmol / L, 1.00 pmol / L, 10.0 pmol / L, 100.0 pmol / L, 1.0 nmol / L, 10.0 nmol / L, 100.0 nmol / L, 1.0 μmol / L, and 10.0 μmol / L. The parameters for the cyclic voltammetry test are: voltage range of 0-1.05 V, scan rate of 75-125 mV / s; The parameters for the square wave voltammetry detection are: frequency 5-15Hz, amplitude 10-30 mV, step potential 3-7mV, oxidation potential range 0.2-0.7 V, and reduction potential range 0.7-0.2 V. The samples were food and environmental samples.

Citation Information

Patent Citations

  • Sodium iodide probe assisted gold nanoparticle-polyarginine-polylysine electrochemical sensor and application thereof

    CN120468242A